Trabalho e educação báasica de jovens e adultos: uma avaliação de como os trabalhadores são remunerados de acordo com as diferentes opções de estudo - Alvarez, Thiago Lobato (2006)
Today s labor market is going through a deep transformation. New technologies and the advance of the knowledge society point to a future in which the market will require increasingly qualified workers. In spite of this fact, 60% of the Brazilian population aged fifteen or more has not completed primary school (equivalent to eight years of studies) and approximately 16 million Brazilians cannot read or write. With this in mind, the purpose of this research was to analyze how the labor market values, through monthly earnings, the different options of study for youths and adults who did not complete secondary school (equivalent to 11 years of study). For this, data of the Pesquisa Mensal de Emprego (Monthly Employment Research, made by the Brazilian Institute of Geography - IBGE) were used, in the period from January 2003 to October 2005. It was possible to verify that workers without schooling who decide to study have lower earnings than workers who do not study. Being able to read and write is the most valued characteristic in the labor market for workers with up to four years of study. Finally, students who attended regular courses showed equal or slightly higher earnings than students attending courses specially designed for those young and adults that have not concluded school at the appropriate age. Based on these data, this work discusses the possible implications in public policies. Interviews were also made at the end of the quantitative research, trying to better understand the relation between work and education of youths and adults. These interviews enabled an analysis of the conflicts that are inherent to this relation